Producción de papa (solanum tuberosum) variedad fripapa bajo tres sistemas de riego. Quevedo - Álvarez Álvarez, Judith Elizabeth (2013)
The present investigation was to evaluate the production of Fripapa (Solanum tuberosum) variety under three irrigation systems. Irrigation systems were used: Gravity irrigation, sprinkler and drip irrigation. Was performed in Cruzpamba neighborhood, St. Andrew Parish, Canton Píllaro, Tungurahua Province, whose geographical location is 1º09´34´´ South Latitude and 78º35´28´´ of West Longitude. The experimental design was a D.C.A. (Complete Randomized Design) with 3 treatments and 6 replications. The best treatment in production of potato (Solanum tuberosum) variety Fripapa under three irrigation systems, is the T3 (Drip irrigation). The economic analysis showed that treatment with the lower production cost/kg and higher net income is the T3 (Drip irrigation), and treatment with higher production cost/kg and lower net income is the T1 (Irrigation by gravity).